Authoring adaptive soft skill simulations - Gaffney, Conor (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2013)
This thesis examines the personalisation of online training simulations which are a key modern approach in computer aided education. More specifically it focuses on the difficulties involved in authoring personalised training simulations. The composition of such systems is very difficult which has hampered their wide spread adoption. At present adaptive training simulations can only be authored by programmers working closely with subject matter experts. One of the key ways for adaptive simulations to increase their popularity in online eLearning is to reduce the effort and technical skills required by authors in their development.
Keywords: Computer Science & Statistics, Ph.D.; Ph.D. Trinity College Dublin.